Abiotic CO2 uptake from the atmosphere by semiarid desert soil and its partitioning into soil phases. Issue 14 (21st July 2015) - Liu, Jiabin; Fa, Keyu; Zhang, Yuqing; Wu, Bin; Qin, Shugao; Jia, Xin
Abstract: Deserts may show strong downward CO2 fluxes and thus could be a significant carbon sink. However, this hypothesis has been strongly challenged because of the failure to determine both the reliability of flux measurements and the exact location of fixed carbon. In this study, we added 13 CO2 to natural (unsterilized) soil in the Mu Us Desert in northern China and quantified the partitioning of added 13 CO2 into soil solid and vapor phases. Results show that natural desert soil absorbed 13 CO2 at a mean rate of 0.28 g m −2  d −1 . Of the absorbed 13 CO2, 7.1% was released over a 48 h period after 13 CO2 feeding, 72.8% was stored in the soil solid phase, 0.0007% was found in the vapor phase, while 20.0% of the absorbed 13 CO2 was undetected. These results indicate that undisturbed desert soils can absorb CO2 from the atmosphere, with the majority of fixed carbon conserved in the soil solid phase. Key Points: We added 13 CO2 to natural (unsterilized) desert soil Soil absorbed 13 CO2 at a mean rate of 0.28g m −1  d −1 The majority of fixed carbon was conserved in the soil solid phase